2016
DOI: 10.5603/gp.2016.0018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characteristics related to parametrial involvement in clinical early-stage cervical cancer

Abstract: Objectives: Since parametrial involvement is believed to be a crucial factor in the management of cervical cancer, our study was designed to investigate the clinical and pathological features which predicted parametrial involvement in patients with clinical early-stage cervical cancer. Material and methods:The study included patients with clinical early-stage cervical cancer who underwent radical hysterectomy with pelvic and para-aortic lymphadenectomy between December 2001 and August 2014, at the Hacettepe Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
4
7
0
Order By: Relevance
“…We do not exclude patients with tumour size more than 2cms. We agree with authors reporting that the incidence of parametrial involvement in women with a tumour size of <2 cm is 0.6%, but it increases with larger cancer size (Boyraz et al, 2016). Other clinicians have also suggested that infiltration of less than half of the cervical stroma is the limit for a safe trachelectomy (Bentivegna et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…We do not exclude patients with tumour size more than 2cms. We agree with authors reporting that the incidence of parametrial involvement in women with a tumour size of <2 cm is 0.6%, but it increases with larger cancer size (Boyraz et al, 2016). Other clinicians have also suggested that infiltration of less than half of the cervical stroma is the limit for a safe trachelectomy (Bentivegna et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…However, the bone manifestation is rare in cervical cancer patients. The rates of bone metastasis in cervical cancer patients with early-stage and advanced stage were reported from 4.0 to 22.9% (16)(17)(18)(19). As for bone metastasis, vertebral column is the most frequent site, particularly the lumbar spine (20).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, among the cases that were classified as stage IA in the FIGO 2018 classification, only one case (11.1%) had LVSI, and no cases had parametrial invasion; this is compatible with previous reports. The presence of LVSI is considered to be associated with parametrial invasion 17 and lymph node metastasis 18 . Thus, pathological findings including LVSI and tumor size seem to be important for accurately diagnosing the stage and estimating the prognosis before hysterectomy, particularly for small tumors.…”
Section: Discussionmentioning
confidence: 99%